Service Quality Improvement Strategy in Library Management at Tadulako University - Prita Andarbeni; Ummu Salamah; Iwan Satibi (Pasundan Social Science Development, 2021)
This study wants to examine how the Tadulako University library can improve its services to users through the development of a strategic plan. It aims to: (1) study and analyzes the quality of services using Tangible dimensions measurement methods (physical appearance), Reliability, Responsiveness, Assurance, and Empathy in the management of services at the University Tadulako; and (2) find strategies to improve the quality of services in the Tadulako University library management. The quantitative and qualitative (mix method) approaches are used in this study to obtain comprehensive, valid, reliable, and objective data. The service quality model uses the Servqual by Zeitham et al. In addition, a descriptive analysis approach is used to provide a description of the research subjects based on variable data. The number of samples is 397 people determined using the Slovin formula, with proportional sampling techniques. The data analysis technique used is the Mathew B. Miles and A. Michael Huberman analysis model. The data validity techniques used include (1) extension of participation; (2) perseverance/grace; and (3) triangulation. Testing research data through validity testing uses product-moment correlation, while reliability testing uses the Alpha-Cronbach method. Data collection techniques used are questionnaires, participant observation, in-depth interviews, documentation, and triangulation. The results of this study show that to improve the quality of service it needs to consider five dimensions of Servqual such as facilities and infrastructure that support service performance, reliability, and responsiveness of officers in serving and helping users who need information quickly and accurately. Providing guarantees of ease in the service process and security guarantees in the library building. The strategy for developing the external environment is done by giving library staff the opportunity to participate in education and training on libraries, collaboration with other universities, improving the quality of IT-based services, and making libraries centers of information for users. While the development of the internal environment is done by improving the quality of library service systems, optimizing the addition of facilities and infrastructure such as update collections, and providing the appropriate formation of human resources in the library so that service can be optimized. A research novelty is an information packaging dimension that supports the improvement of online-based library service quality systems